Well‐Defined High‐Molecular‐Weight Polyacrylonitrile Formation via Visible‐Light‐Induced Metal‐Free Radical Polymerization. Issue 15 (19th May 2017) - Niu, Tengfei; Jiang, Jiayu; Li, Siyuan; Ni, Bangqing; Liu, Xuemin; Chen, Mingqing
Abstract : In this paper, well‐defined high‐molecular‐weight polyacrylonitrile (PAN) is successfully synthesized by visible light promoted metal‐free radical process at room temperature. The approach provides the final molecular weight of the PAN more than 150 × 10 3 g mol −1 and polydispersity index of only 1.29. MALDI‐TOF MS and 19 F NMR spectroscopy indicate the F‐chain‐end process. This new approach allows for the efficient synthesis of well‐defined random copolymers. Abstract : Polyacrylonitrile (PAN) with high molecular weight and low dispersity is successfully synthesized by visible‐light‐induced metal‐free radical polymerization at room temperature. This polymerization technique uses organic dye Eosin Y as photocatalyst and benzenediazonium tetrafluoroborates as initiator. Gel permeation chromatography‐multiangle laser light scattering shows the absolute molar weight of the PAN more than 1.50 × 10 5 g mol −1 with a polydispersity index < 1.3 while MALDI‐TOF MS and 19 F NMR spectroscopy indicate the F‐chain‐end process. The first‐order kinetic behavior, molecular weight distributions shifting, and "ON/OFF" experiment results suggest this reaction may follow the atom‐transfer‐like radical polymerization mechanism. In addition, this new approach allows for the efficient synthesis of well‐defined random copolymers.